Study on Regional Development Work Environment Panjang Port Lands in Support Bandar Lampung City As A Service and Trade - A. Iksan Karim; Yohn Ferry (Bandar Lampung University (UBL), 2013)
This study provides an overview of the development area work at the mainland port of Panjang survey from the physical to the room which is supported by the economic and socio-cultural aspects as well as driving the development of Bandar Lampung city as background underlying this study is the role of the port of Panjang in support of the Bandar Lampung city services and trade approach is the research done by using quantitative descriptive analysis and sampling, is to perform analysis based on primary and secondary data that aim to determine the condition penlitian growing region during the period of 2000 to 2009, working environment inland port Panjang area had been developed significant physical changes spasila concerns that are affected by changes in economic and social change in communities characterized by higher population growth are likely to lead to the distribution of population and territory outside research, adnaya shift in population composition eyed pecarian characterized by the use of physical changes on regional spassial transport path with a tendency to be a place of business houses. Thus the direction of physical development spasila research area with a linear pattern, the developments along the transport path. During the period 2000 - 2004, Bandar Lampung city experienced significant developments concerning three aspects to be investigated. Physical development of the city of Bandar Lampung reflected by high household changes from being a place of business and any changes - changes in population distribution are likely to lead to the city center, adnaya composition of population by increasing livelihood is Trade and services sector, based on the economic development of Bandar Lampung greatly influenced the area interlandnya because the study area is very close to other cities. Physical development of the city of Bandar Lampung is the result of socio-economic and cultural development of the city of Bandar Lampung who influence the use of space. Developments in this period was the submarine structure linear shaped urban space, as a motivating factor, especially the development of Bandar Lampung is a port city is also an increase in the role of Bandar Lampung city became important for the surrounding area, with the development of non-primary economic activity, as well as the relationship economy with surrounding areas and airports Lampung City is currently the largest city in the province of Lampung as well as the Provincial Capital and Provincial Government